(untitled) (Seminário Internacional de Informação, Tecnologia e Inovação, 2023)
Social inclusion is a pressing activity in our midst, signaling the commitment of people and institutions to share access to all resources available to individuals with disabilities. This study aimed to identify the procedures developed by the Accessibility Center of the Federal University of Alagoas for the inclusion of people with disabilities in the university’s pedagogical process. The methodology to be used will be guided by a descriptive and exploratory qualitative approach, using bibliographical research and local visits, presenting at the end, the results obtained and indicating suggestions to better serve these students with special needs.